Se um viajante numa noite de inverno, de Italo Calvino, e a questão da leitura - Thomé, Talyta Teixeira (2021)
The present dissertation deals with the study of the novel Se um viajante numa noite de inverno, by Italo Calvino, the light of the theories of reading and the novel. It aims to analyze the characters and their relations with reading and searches for the sequences of unfinished books with which they come into contact throughout the narrative. It also has, as a secondary objective, an analysis of this novel written by Calvino, since a plural and peculiar novel is observed. Through authors such as Bournneuf and Ouellet (1976), Bakhtin (2016), Reis (2013, 2018), Candido et. al. (1968), Brait (2006), among others, it was possible to construct a theoretical contribution about the novel and the characters, in order to reinforce the analysis that raised the presence of these narrative and fictional elements in Calvin's book. Authors such as Machado (2016), Petrucci (1999), Eco (1983, 2005, 2011, 2018), Zumthor (2018), Manguel (2017), Azevedo (2004), Lajolo and Zilberman (2019), Compagnon (1999), among others, they were used to structure the theoretical discussion about reading and readers, in order to reaffirm the already analyzed elements that were perceived in Calvino's novel. Thus, the research was developed observing the following order: a) theoretical discussion about romance and character; b) theoretical discussion about reading and readers; and c) the analysis of Calvino's work through reflections taken from the book's structure and history and reaffirmed by theories.